MORPHO-FUNCTIONAL CHARACTERISTICS OF THE PINEAL GLAND AT THE SIMULATION LAUNDRY LIGHTING COVERAGE AND ACUTE STRESS - V. V. Pshychenko (Кубанский научный медицинский вестник, 2014)
Conduct a study on the morpho-functional features of the pineal gland at the simulation laundry lighting and acute stress. It was determined that in the peripheral regions of the pineal gland conditions develop functional activity, as indicated by illumination of the region, as compared with the central part, by reducing the number of basophilic nuclei substance pinealocytes. These morphological features suggest a low functional activity of the pineal gland of rats under experimental conditions.